Enhanced optical output of InGaN/GaN near-ultraviolet light-emitting diodes by localized surface plasmon of colloidal silver nanoparticles. (25th September 2015) - Hong, Sang-Hyun; Kim, Jae-Joon; Kang, Jang-Won; Jung, Yen-Sook; Kim, Dong-Yu; Yim, Sang-Youp; Park, Seong-Ju
Abstract We report on the characteristics of localized surface plasmon (LSP)-enhanced near-ultraviolet light-emitting diodes (NUV-LEDs) fabricated by using colloidal silver (Ag) nanoparticles (NPs). Colloidal Ag NPs were deposited on the 20 nm thick p-GaN spacer layer using a spray process. The optical output power of NUV-LEDs with colloidal Ag NPs was increased by 48.7% at 20 mA compared with NUV-LEDs without colloidal Ag NPs. The enhancement was attributed to increased internal quantum efficiency caused by the resonance coupling between excitons in the multiple quantum wells and the LSPs in the Ag NPs.